Rapid prototyping of high performance sportswear - Chowdhury, H.; Alam, F.; Mainwaring, D.; Beneyto-Ferre, J.; Tate, M. (Procedia Engineering, 2012)
The athlete outfit plays a vital role in wide range of sports especially in high speed sports including cycling, skiing, bobsleigh, sprint, speed skating and swimming as small time margins in those sports makes a difference between the winner and loser. Performance of the sportswear greatly depends on aerodynamic or hydrodynamic, thermodynamic properties, including the fitting of the sportswear to the athlete body. Development of a high performance sportswear is not only expensive but also time consuming. Therefore, a computer aided rapid prototyping process for manufacturing of high performance sportswear can save both time and money. In order to rapid prototype sportswear, modern computer technology can be utilized. This paper describes a methodology starting from the 3D scanning of an athlete body to a prototype design of high performance sportswear. In this study, rapid prototyping of a high performance ski jumping suit has been described.